Performance of composites via multiple interface engineering techniques: plasma etching, UV-induced grafting and nanotube deposition. (March 2020) - Zhang, Ce; Pei, Xiaoyuan; Xu, Zhiwei; Wang, Chunhong; Zhang, Guoli; Guo, Xingfeng; Fu, Hongjun; Wu, Ning
Abstract: We systematically investigate interfacial modification mechanisms on interfacial structure, mechanical and anti-fatigue performances of carbon fiber/epoxy (CF/EP) composites. The same interfacial shear strength (IFSS) was achieved by reasonable experiment design based on three explored mechanisms: (i) Ar plasma treatment for mechanical interlocking mechanism, (ii) UV-induced grafting acrylic acid for chemical bonding effect and (iii) carbon nanotubes electrophoretic deposition for transition layer theory. We found that the interface layer thickness and modulus of composites vary greatly due to different interfacial modification mechanisms. The damage resistance can be improved by increasing the propagation paths or hindering the propagation direction of the destructive cracks. Under the condition of the same interfacial strength, the variation trend of mechanical strength and fatigue properties were signfificantly different owing to the different interface microstructure. The nanotube deposition method has advantages in flexural strength, tensile strength and storage modulus, because the formed gradient interface layer has the dual effects of strengthening, toughening resin and increasing stress transfer efficiency. Plasma etching method is superior to the other two methods in residual bending strength retention because the mechanical interlocking in the interface micro-region can improve the stiffness of the composite and hinder the propagation of cracks. UV-induced grafting method is beneficial in improving the tensile strength of composites, because it has low damage to the mechanical strength of fiber. Therefore, when the interfacial strength is the same, carbon nanotubes electrophoretic deposition among the three modification methods has more attractive application prospects.